Race, racism, and empire: reflections on Canada - Dua, Enakshi (Social justice, 2005)
A special issue on race, racism, and empire in the Canadian context. Articles discuss geopolitics, culture clash, and gender after the terrorist attacks of September 11, 2001; the disciplinary boundaries of Canadian identity after September 11; race, gender, and nation in The Globe and Mail after September 11; “race”-sex anxieties and alternative globalizations; spatialized location, identities, and nationality in international work; racial hierarchies in transnational call center work; decolonizing antiracism; reflections on class and race; race, class, and gender in the lives of elite Chinese-Canadian women; and Africa in Canadian academic libraries. An introduction to the special issue is also provided.